Present status of the positive space charge lense for focusing intense negative charged particle beams - Goncharov, A.A.; Dobrovolskiy, A.M.; Dunets, S.M.; Litovko, I.V.; Gushenets, V.I.; Oks, E.M.; Bugaev, A.S. (Вопросы атомной науки и техники, 2012)
We describe the new experimental and simulation results of wide-aperture (6 cm) non-relativistic (up to 18 keV) intense (up to 400 mA) electron beam focusing by the positive-space-charge plasma lens. Recently we proposed and explored a new original plasma-optical tool for negative charged particle beams focusing and manipulating with a dynamic cloud of non-magnetized free positive ions and magnetically isolated electrons produced by a toroidal plasma source like an anode layer thruster. In such kind systems the electrons are separated from ions by relatively strong magnetic field in the discharge channel. The accelerated ions are weakly affected by the magnetic field owing to their mass. Focusing of the electron beam by electrostatic plasma lens was separated from magnetic focusing experimentally and the compression factor was up to about 5. The results of the computer simulation are shown good agreement with experimental data. Obtained experimental results demonstrate the possibility to create a lowcost high-effective tool for negatively-charged particle beam focusing without influence of momentum aberrations. Впервые наглядно продемонстрирован эффект фокусировки интенсивного широкоапертурного электронного пучка средних энергий электростатической плазменной линзой формирующей аксиально-симметричное облако положительного пространственного заряда в области прохождения пучка в условиях магнитной изоляции плазменных электронов линзы. Экспериментально измеренное фокусное расстояние плазменной линзы находится в согласии с расчетным значением. Достигнуто почти пятикратное увеличение плотности тока пучка на оси при совместном действии магнитного и электростатического полей линзы. Показана возможность четкой сепарации влияния магнитного и электрического полей на фокусировку проходящего электронного пучка. Вперше наочно продемонстровано ефект фокусування інтенсивного широкоапертурного електронного пучка середніх енергій електростатичною плазмовою лінзою, що формує аксіально-симетричну хмару позитивного просторового заряду в області проходження пучка в умовах магнітної ізоляції плазмових електронів лінзи. Експериментально виміряна фокусна відстань плазмової лінзи знаходиться у згоді з розрахунковим значенням. Досягнуто майже п’ятикратне збільшення густини струму пучка на осі при суміснїй дії магнітного та електростатичного полів лінзи. Показана спроможність виразної сепарації впливу магнітного і електричного полів на фокусування електронного пучка, що проходить.